Confronting fascism in Egypt : dictatorship versus democracy in the 1930s - Gershoni, I. (Stanford University Press, 2010)
A new reading of the political and intellectual culture of Egypt during the interwar era. Though scholarship has commonly emphasized Arab political and military support of Axis powers, this work reveals that the shapers of Egyptian public opinion were largely unreceptive to fascism, openly rejecting totalitarian ideas and practices, Nazi racism, and Italy's and Germany's expansionist and imperialist agendas.